2004
DOI: 10.1080/03008200490278115
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Alpha-2 Macroglobulin on the Healing of Ruptured Anterior Cruciate Ligament in Rabbits

Abstract: To investigate the effect of modification of biological environmental conditions, one of the factors influencing the healing of anterior cruciate ligament rupture, we performed experimental anterior cruciate ligament ruptures on New Zealand rabbits. After experimental rupture, intra-articular alpha-2 macroglobulin was injected into the knees of the rabbits in the experiment group to prevent structural changes resulting from the enzymatic reactions in the ruptured anterior cruciate ligament. At the end of 10th … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2005
2005
2025
2025

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…Studies have shown that A2M inhibits the activities of ADAMTS-4, ADAMTS-5, ADAMTS-7, and ADAMTS-12 [21, 22], reduces ligament stump resorption following ACL injury [15], and enhances tendon-bone healing of ACL grafts by inhibiting MMP-13 activity [16]. Thus, the balance of the protease/A2M in vivo may play an important role in mediating cartilage destruction by catabolic enzymes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that A2M inhibits the activities of ADAMTS-4, ADAMTS-5, ADAMTS-7, and ADAMTS-12 [21, 22], reduces ligament stump resorption following ACL injury [15], and enhances tendon-bone healing of ACL grafts by inhibiting MMP-13 activity [16]. Thus, the balance of the protease/A2M in vivo may play an important role in mediating cartilage destruction by catabolic enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Higher A2M concentration is associated with lower MMP-13 content [5]. The difference is thought to be due to the large molecular weight of A2M, which prevents it’s migration from the blood into the SF [14, 15]. Thus, supplemental A2M may be a potential strategy to attenuate cartilage degeneration by reducing these catabolic enzymes induced by joint injury.…”
Section: Discussionmentioning
confidence: 99%
“…The same procedure was repeated on the first postoperative day. The dose of α 2 -macroglobulin used for the present study was based on previously reported histological results 19 .…”
Section: Methodsmentioning
confidence: 99%
“…High and low levels of A2M have been found in blood and synovial joints, respectively, due to the large molecular weight of A2M, which prevents its migration from blood into the synovial fluid (SF) . Thus, supplemental A2M may be a potential strategy to attenuate cartilage degeneration by reducing these catabolic enzymes induced by joint inflammation.…”
Section: Discussionmentioning
confidence: 99%